A Study of Job Motivation, Quality of Work Life and Work Performance Amongst Teachers in the Republic of Maldives - Ashraf, Abdul Raheem (2015)
The thesis discusses the job motivation, quality of work life and work performance amongst the teachers in the Republic of Maldives. Owing to the implications of the Civil Service Act in 2008, there has been a tremendous change in the educational standards in the country compared to its neighbor countries. One of the changes related to the teaching community in the country. The analysis of the research shows that situation is more severe in government school than in private schools. Owing to these issues, there has been a constant migration of staff from the government to the private educational sector. However, the researcher believes that even in such a situation, the staff are contributing their best effort to provide quality education in government schools in the country. Therefore, the study selected four government schools in Maldives for collecting the primary data. Using qualitative and quantitative methods of research, the study considered two types of respondent; i) teaching/administrative staffs and ii) Head-of-School/Ex-Principals. The data were collected and a pilot study was conducted to understand the effectiveness of the questionnaire been designed. Based on the outcome of the pilot study, the survey tool was amended to gather more precise and accurate data. After collecting the final data, statistical analysis was performed on the primary data to test the study‘s hypothesis. The outcome of the study shows some of the latent facts which were never reported in media or in any research paper. A significant limitation in the educational system in the Republic of Maldives has been found in the outcome which has negatively affected; i) job motivation, ii) quality of work life, as well as iii) work performance of the teaching community in the country.